Production And Efficacy Of Exserohilum Longirostratum As A Bioherbicide For The Control Of Itch Grass (Rottboellia Cochinchinensis) In Sugarcane Farms - Alester A. Abi, Charles Borromeo (2008)

(untitled)
Itch grass or Rottboellia cochinchinensis (Lour.) W.D. Clayton is considered as on of the most important weeds in tropical countries. Integrated weed management is a tool-box of options that can be tailored to individual farm, cropping and weed situations. Biological control is one of these management options, therefore the production method and field efficacy of Exserohilum longirostratum as a bioherbicide to control itch grass in sugarcane was investigated. The growth and sporulation of E. longirostratum was excellent in media strength at recommended rate (200ml V8juice + 800ml H2O). The optimum pH for conidia production and conidia germination was in the range of pH 6 – 7. The conidia stored in liquid suspension (water and oil) and freeze-dry failed to germinate. Air dried conidia in powder formed stored at 70C and 200C has germination rate of 80% and remained viable for 6 months in comparison to those stored at other temperature levels. The conidia stored at 1 % Relative Humidity (RH) (silica gel) remained viable for more than 6 months with germination rate of 80%. Deterioration of conidia stored at 1% RH was slow (rL = -0.41064) compared to those stored at 96.5% RH using K2SO4 saturated solution where the rate of deterioration was significantly fast (rL = -0.73). Susceptibility of several sugarcane varieties towards E. longirostratum were tested using 1x107/ml conidia concentration, and the results indicated that all sugarcane varieties tested were resistant to E. longirostratum as indicated by lower values of area under disease progress curve (AUDPC) and decreasing rates of disease progress. Sugarcane variety 95R-1004 was selected for the field trials as this variety was newly introduced to be planted at Federal Land Development Authorities (FELDA) in Chuping, Perlis. In this study variety 95R-1004 and itch grass at 6-8 leaf stage were sprayed with 107,108 and 109 conidia/ml concentrations in 10% of oil emulsion. Plants were sprayed three times at interval of 1 week. The three applications treatment of E. longirostratum at 109 conidia/ml provided excellent control (100% mortality) of R. cochinchinensis compared to the other treatments as shown by higher AUDPC value (1168 units) and faster disease progress rate (rL 0.61 unit/day). There was no significant difference in tiller numbers and the growth of sugarcane between the inoculated plots and the untreated control or plots treated with the fungus-free oil emulsion. The dry weight of itch grass was highest when treated with fungus-free oil emulsion (0.275kg) or untreated controls (0.290kg). None of the itch grass plants survived in plots treated with chemical herbicide (BASTA®), or plots with E. longirostratum. The sugarcane dry weight was significantly high (1.6kg) in plots treated with E. longirostratum at 109 conidia/ml compared to the other treatments. This may be due to eradication of itch grass in this treatment earlier than in the other treatments, thus there was no competition between sugarcane and itch grass, resulting in a faster growth of the sugarcane plants. This research indicated that E. longirostratum has an ability to provide excellent control of R. cochinchinensis at 6-8 leaf stage under field conditions.